Favela não é o lugar, são as pessoas . Desconstruindo a relação entre lugar e violência no Sarney e no Japão, Natal/RN - Barbosa Junior, José Duarte (2013)
The city is the privileged place construction of social and political life, and the gathering of social groups. Meeting place, the diversity and possibilities. But the urban universe which cities belong is not a homogeneous whole. There are spaces demarcated and valued ideologically creating antithetical images about places that are now recognized as violent or dangerous. Peripheral urban situations of unprivileged add to theprejudices to the origin of place within the neighborlyallotments José Sarney and Novo Horizonte (Japan Slum) / Natal-RN, which are reproduced in narratives of everyday life. Spatial divisions are exploited, mixed and repeated to maintain social distances through rites of separations and dichotomies such as neighborhood/joint housing, allotment/slum and the people of the high place/the people of the down place. Social categories such as buraco(hole) and cabras (goats) are evoked to interpret the world of violence and places regarded as dangerous. The prominence of hypermasculinity and perception of children and adolescents living on the outer elements are brought up to the interpretation of images evoked in interviews with residents and their neighbors